Equilibrium Isotherm Study Of Cr(VI) Adsorption Using Peanut Shells (Arachis Hypogaea L.) Activated by Ethanol-Toluene Mixture - I Nyoman Sukarta; Gede Andika Wijaya (International Journal of Applied Chemistry Research, 2021)
This study aimed to study the adsorption of Cr(VI) by activated peanut shells using a mixture of ethanol-toluene (1:1). Cr(VI) was measured using a Shimadzu Atomic Adsorption Spectrophotometer (AAS). The results showed that the adsorption power of Cr (VI) by peanut shells was 69.56% at a concentration of 10 ppm. The adsorption characteristics of Cr (VI) by peanut shells were consistent with the Langmuir and Freundlich adsorption isotherm patterns. Meanwhile, the maximum adsorption power of Cr (VI) by activated peanut shells with a mixture of ethanol-toluene (1:1) was 4.0 mg/g.